Novel Strategies for the Control of Wireworm in Potato Crops - Benjamin Clunie (2023)
The biological control of wireworm (Agriotes spp.) in potato crops has not yet caught up to conventional controls at a time in which deregistration of pesticides is increasing, leaving a paucity of options for growers. Some measure of control has been achieved with use of entomopathogenic fungi (EPF), and to a lesser extent, entomopathogenic nematodes (EPN), with varying success. Factors affecting efficacy range from instability of pathogens within a soil matrix to difficulty in accurately targeting a subterranean pest in a heterogeneous population. The overall aim of this project was to identify areas for improvement for biological control strategies for wireworm, through identification of bioactive compounds and exploring synergies between these and existing entomopathogens. Using historical research to identify botanical extracts for bioactivity against invertebrate pests, tea tree (Melaleuca alternifolia) and rosemary (Salvia rosemarinus) oils were found to elicit repellent properties in wireworm, positively associated with mortality. Cedarwood (Cedrus atlantica) oil produced the opposite effect, an attractant response with no adverse effects on larval health. The second aspect of the project posited a novel behavioural assay methodology, demonstrating wireworm plant preferences and complex behavioural responses to introduced botanical semiochemicals beyond that of a simple attraction or repulsion. Identified botanicals were then evaluated for compatibility with strains of Metarhizium brunneum, with each of the three exhibiting fungicidal and fungistatic effects on the EPF, but at lower concentrations improving mortality and rate of pathogenicity. Finally, wireworm behavioural responses to EPF inoculations were exploited with two fungal volatile organic compounds (VOC), 1-octen-3-ol and 3-Octanone, found to have direct bioactivity towards wireworm and marginal synergistic effects with a known biological control in the entomopathogenic nematode, Heterorhabiditis bacteriophora. The project has clearly demonstrated methods for improvement for existing biological controls and given strong evidence for use of botanicals as crop protectant compounds in an integration pest management system for potato crops.